2020
DOI: 10.3390/ma13132956
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Load-Carrying Capacity of Thin-Walled FRP Composite Z-Profiles under Eccentric Compression

Abstract: This study investigates the effect of eccentric compressive load on the stability, critical states and load-carrying capacity of thin-walled composite Z-profiles. Short thin-walled columns made of carbon fiber-reinforced plastic composite material fabricated by the autoclave technique are examined. In experimental tests, the thin-walled structures were compressed until a loss of their load-carrying capacity was obtained. The test parameters were measured to describe the structure’s behavior, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Carbon fiber/epoxy (EP137-CR527/100-35) material was prepared using a standard autoclave curing process. The laminate manufacturing process was carried out under special and sterile conditions [ 30 ].…”
Section: Experimental Testsmentioning
confidence: 99%
“…Carbon fiber/epoxy (EP137-CR527/100-35) material was prepared using a standard autoclave curing process. The laminate manufacturing process was carried out under special and sterile conditions [ 30 ].…”
Section: Experimental Testsmentioning
confidence: 99%
“…However, CFRP structures present some drawbacks; their properties and performance are highly dependent on the number of CF fabric layers (Vf) used, their orientation in ply level, and the polymer’s matrix characteristics [ 3 ]. When external loads are applied, such as compression forces, phenomena like fibre and matrix breakage, delamination between plies, and/or fibre buckling can occur, leading to reduction of performance or even breakage of the composite structure [ 4 , 5 ]. Production of composite structures constantly increases; however, at the same time, large quantities of scrap are being produced during manufacturing and, in most cases, disposed to landfill or incinerated, leading to severe environmental impacts [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, although the loss of stability of these members may result in a localized weakening of the load-bearing structure, it does not affect the immediate risks to the safe use of such a construction [ 8 , 9 , 10 , 11 ]. Available research has shown that thin-walled composite members can still carry loads in the buckling state, provided that the buckling is elastic and the equilibrium path after buckling is stable [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Therefore, in addition to investigating member buckling, it is also necessary to investigate the buckling behavior of the entire structure and its buckling capacity.…”
Section: Introductionmentioning
confidence: 99%